Non‐immune fetal hydrops: etiology and outcome according to gestational age at diagnosis. (7th August 2020) - Sileo, F. G.; Kulkarni, A.; Branescu, I.; Homfray, T.; Dempsey, E.; Mansour, S.; Thilaganathan, B.; Bhide, A.; Khalil, A.
ABSTRACT: Objective: Fetal hydrops is associated with increased perinatal morbidity and mortality. The etiology and outcome of fetal hydrops may differ according to the gestational age at diagnosis. The aim of this study was to evaluate the cause, evolution and outcome of non‐immune fetal hydrops (NIFH), according to the gestational age at diagnosis. Methods: This was a retrospective cohort study of all singleton pregnancies complicated by NIFH, at the Fetal Medicine Unit at St George's University Hospital, London, UK, between 2000 and 2018. All fetuses had detailed anomaly and cardiac ultrasound scans, karyotyping and infection screening. Prenatal diagnostic and therapeutic intervention, gestational age at diagnosis and delivery, as well as pregnancy outcome, were recorded. Regression analysis was used to test for potential association between possible risk factors and perinatal mortality. Results: We included 273 fetuses with NIFH. The etiology of the condition varied significantly in the three trimesters. Excluding 30 women who declined invasive testing, the cause of NIFH was defined as unknown in 62 of the remaining 243 cases (25.5%). Chromosomal aneuploidy was the most common cause of NIFH in the first trimester. It continued to be a significant etiologic factor in the second trimester, along with congenital infection. In the third trimester, the most common etiology was cardiovascular abnormality. Among the 152 (55.7%) women continuing the pregnancy, 48 (31.6%) underwent fetal intervention, including the insertion of pleuroamniotic shunts, fetal blood transfusion and thoracentesis. Fetal intervention was associated significantly with lower perinatal mortality (odds ratio (OR), 0.30 (95% CI, 0.14–0.61); P < 0.001); this association remained significant after excluding cases with a diagnosis of anemia or infection (OR, 0.29 (95% CI, 0.13–0.66); P = 0.003). In 104 fetuses not undergoing active fetal intervention, the gestational age at diagnosis was the only parameter that was significantly associated with the risk of perinatal mortality (OR, 0.92 (95% CI, 0.85–0.99); P = 0.035), while the affected body cavity and polyhydramnios were not ( P > 0.05). Conclusions: An earlier gestational age at diagnosis of NIFH was associated with an increased risk of aneuploidy and worse pregnancy outcome, including a higher risk of perinatal loss. Fetal therapy was associated significantly with lower perinatal mortality. © 2020 Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of International Society of Ultrasound in Obstetrics and Gynecology.